A family outbreak of mumps: clinical observation - L. U. Ulukhanova; P. M. Ibrahimova; M. A. Ninalalov; N. S. Karnaeva (LLC "Diagnostics and Vaccines", 2024)
The article presents a clinical case of a family outbreak of mumps that fell ill at the same time (there are 8 children in the family, the first child, 17 years old, vaccinated, did not get sick, the eighth was 3 months old, healthy), four out of six cases were complicated by serous meningitis. Mumps infection is characterized by a high susceptibility of non-immune individuals, with the accumulation of which massive foci form in organized groups, which gives the incidence of mumps an outbreak character.